1977
DOI: 10.1037/0022-0167.24.6.503
|View full text |Cite
|
Sign up to set email alerts
|

Use of behavioral versus traditional procedures for increasing job interview skills.

Abstract: The improvement of job interview skills was studied using 45 paid student volunteers who were drawn equally from business administration and nursing. The students were randomly divided among a behavior training group, a traditional discussion training group, and a control group. Before and after training, all of the students completed a videotaped simulated job interview, which was independently rated by two judges for length of eye contact, length of response, voice affect, loudness of voice, ability to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…al, (1968) and Stevens and Tornatzky (1976) studies, all studies involved ratings of interview behaviors in simulated job interviews by either trained raters or practicing personnel managers. In addition, two studies (Austin & Grant, 1981;Hollandsworth et. al., 1977) employed self-ratings of interview performance, while the Hollandsworth et.…”
Section: Criterion Variablesmentioning
confidence: 96%
See 1 more Smart Citation
“…al, (1968) and Stevens and Tornatzky (1976) studies, all studies involved ratings of interview behaviors in simulated job interviews by either trained raters or practicing personnel managers. In addition, two studies (Austin & Grant, 1981;Hollandsworth et. al., 1977) employed self-ratings of interview performance, while the Hollandsworth et.…”
Section: Criterion Variablesmentioning
confidence: 96%
“…Ratings by a personnel manager showed increases in the four global areas of enthusiasm, positive information conveyed, ambition, and the probability of hire. Hollandsworth, Dressel, and Stevens (1977) assessed the effectiveness of behavioral and discussion training for increasing job interview skills among college seniors. Using a pretest and posttest control group design, Hollandsworth, Dressel, and Stevens found that subjects who received behavioral training (modeling, response rehearsal, directed feedback) exhibited a greater increase in the percentage of eye contact than either the discussion or control group.…”
Section: Rehabilitation Clientsmentioning
confidence: 99%
“…A six-month follow up showed no significant attitudinal differences between the two groups but those who participated in the interview workshop obtained higher paying jobs. Hollandsworth, Dressel, and Stevens (1977) developed a job interviewee skills workshop based on behavioral procedures such as modeling, role playing, and directive feedback, and compared it with a traditional lecture-discussion group approach, as well as with a no-treatment control group. .…”
Section: Intervie Wee Trainingmentioning
confidence: 99%
“…In addition, several controlled investigations have supported the effectiveness of this approach Hollandsworth, Dressel, and Stevens, 1977;Keil and Barbee, 1973). Other studies in the area of social-skills training also appear to be directly applicable to the job-interview setting.…”
mentioning
confidence: 90%